COMPLIANCE LEVEL OF IMPLEMENTATION OF OCCUPTIONAL SAFETY AND HEALTH MANAGEMENT SYSTEM (SMK3) IN CONCRETE WORKSHOP DEPARTMENT OF BUILDING CONSTRUCTION, SANITATION AND MAINTENANCE (KGSP) OF SMK NEGERI 1 PALANGKA RAYA - Doni Setiawan; Revianti Coenraad (Jurusan Pendidikan Teknologi Dan Kejuruan, 2020)
This study aims to find out the complete facilities of Personal Protective Equipment (PPE) and Workshop Safety in accordance with school standards and the Compliance Level of Implementation of Occupational Safety and Health Management System (SMK3) in Concrete Workshop, Building Construction, Sanitation and Maintenance (KGSP) SMK Negeri 1 Palangka Raya. Based on the results of the indicator achievement in the completeness of Personal Protective Equipment (PPE) and Workshop Safety at Concrete Workshop, Department of Building Construction, Sanitation and Maintenance (KGSP) of SMK Negeri 1 Palangka Raya, it has 49.9% of achievement with less criteria. This will be the evaluation reference and the follow-up for workshops and schools to provide more attention on the protection facilities being more complete. Whereas the achievement of the Occupational Health and Safety Management System in the Concrete Workshop, Building, Sanitation and Maintenance (KGSP) Department which is 63.1% has entered into sufficient categories. Due to the implementation of K3 has been achieved, it is necessary to increase the implementation of K3 in accordance with the K3 management system.